INTOLERANSI MENURUT TOKOH AGAMA ISLAM DAN KRISTEN - Kamaluddin Kamaluddin; Ismet Sari; Mimi Anggraini (Studia Sosia Religia, 2021)
AbstrackIndonesia is a nation that has a diversity of religions, races, ethnicities and languages. Scientifically, this does not exist to differentiate between one another, instead these differences serve as an adhesive in diversity. In the context of social life, differences in views as a result of historical inheritance have given birth to a grouping of what is called the majority and the minority. Islam as the majority religious group has always been targeted for accusations of acts of intolerance. This study uses a qualitative method, which aims to describe and develop concepts that can explain the phenomena of intolerance that occur. This study uses a phenomenological approach to religion which examines the intolerance that is labeled as Islam objectively and descriptively. The results of this study are that there is no single religion that teaches about acts of intolerance, only teaches about love and peace, besides that all religious leaders play a very important role in conveying the teachings of each of these religions to always spread peace and Islam is a religion that rahmatan lilalamin. Intolerance can arise only from people who do not understand religion properly. The purpose of this research is because many cases of intolerance when examined come from religious communities other than Islam. But the fact that is happening now is when someone talks about intolerance they will definitely say Islam intolerance. So the author draws this theme to be researched with the intention that the phenomenon of a stylistic view of Islam is related to intolerance and cleanses the good name of Islam which is rahmatan lilalamin.Keywords: Intolerance, Religious Figures, Islam, Christianity